The television legal reform in Chile and the digital future: one step forward, one step back - Sierra, Lucas (Law, State and Telecommunications Review, 2010)
This article analyzes the television legal reform proposed by the Chilean Cabinet to the Congress to adapt the TV legal framework to the future digital technology. This reform consists in two propositions: one pertaining to the Law 18,838 (the General Law for TV) and another one to the Law 19,132, which outlines the Chilean National Television. Both propositions are herein scrutinized. I contend that the first proposition contains an important step forward, since it creates a new category of telecommunication services named “intermediary services”. This is a step towards convergence which results from digital technologies in the various telecommunication services, nevertheless further proposed changes limit this path as is the case of establishing must-carry obligations for “public interest campaigns”. The latter proposition is also critized due to its outcome that blurs the Chilean National Television goals that inspires the Chilean economic regulation, such as the state subsidiarity and the equal protection of law in state and private TV enterprises. As a conclusion, the proposed legal framework reform in Chile takes one step forward, but also one step back.